PENGEMBANGAN POLA LATIHAN PENYERANGAN DALAM PERMAINAN BOLAVOLI MENGGUNAKAN MEDIA AUDIO VISUAL PADA TIM BOLAVOLI PUTRI UKM UABV UNIVERSITAS NEGERI MALANG - munhamir, Mochammad Dako Ikul; Supriyadi, Supriyadi; Gatot Sunijantoro, Agus (Jurnal Sport Science, 2015)
Abstract :The pattern of attacks is one of the strategies that must be mastered by a team in a game of volleyball. This research belong to the kind of research and development (research and development) and conceptual research model. the results of the evaluation of exercise patterns in the game of volleyball attack is: 91,05% of the experts of the game of volleyball, 81% of the experts of the game of volleyball, 75% of media experts. The trial results from a small group obtained 89% against 6 athletes and the trial results fron a large groups obtained 88,06% against 30 athletes, so that product development is worth to use the result of product development patterns in the game of volleyball attack exercises to woman team volleyball of UABV State University of Malang, among others: (1) patterns of exercise in the form of audio visual accordance with volleyball woman team UKM UABV State University of Malang, (2) the display pattern drills in assault accompanied by audio visual shows the process of the exercise, (3) products packaged with VCD (Video Compact Disc).Keywords :the pattern of assault, assault Exercise pattern, audio visual Media